Does it pay for women to volunteer? - Robert M. Sauer (Institute for the Study of Labor (IZA), 2012)
This paper estimates the economic and non-economic returns to volunteering for prime-aged women. A woman's decision to engage in unpaid work, and to marry and have children, is formulated as a forward-looking discrete choice dynamic programming problem. Simulated maximum likelihood estimates of the model indicate that an extra year of volunteer experience increases wage offers in part-time work by 8.3% and wage offers in full-time work by 2.4%. The behavioral model also reveals an adverse selection mechanism which is consistent with the negative returns to volunteering found in reduced-form wage regressions. The negative selection is driven by differential unobserved market-productivity and heterogeneous marginal utilities of future consumption. The structural estimates also imply that the economic returns to volunteering are relatively more important than non-economic returns, and introduction of a tax-credit for volunteering-related childcare expenses would substantially increase volunteer labor supply and female lifetime earnings.
Keywords: C35; C53; C61; D91; J12; J13; J22; J24; J31; J64; 330; female labor supply; marriage; fertility; negative selection; attrition; dynamic programming; structural estimation; simulated maximum likelihood; volunteering